Pengembangan Media Pembelajaran Berbasis Augmented Reality Pada Materi Bangun Ruang di Kelas VI SD - Lutfiani, Hajar Asri; Yandari, Indhira Asih Vivi; Yuhana, Yuyu (Universitas Negeri Makassar, 2024)
An essential aspect in learning activities is the use of learnig media. The use of learning media that appropriate for the requirement will create ideal learning. This research aims to develop augmented reality-based learning media on bangun ruang subject at VI grade. The study was conducted at SD Negeri Bojong Rawalumbu VI in Bekasi with 32 six-grade pupils served as the research subjects. This research used the research and development (R&D) method and 4D model. This learning media has been through a validation test with an average percentage of 87.7% by media experts, 97.5% by materiql experts, and 95% by linguists. The results of students’ responses to the augmented reality-based learning media obtained an average percentage of 91%. The conclusion is that augmented reality-based learning